Social factors influence on career choices for female computer science students - Malik, Sohail Iqbal; Al-Emran, Mostafa (IJET, 2018)
The low and shrinking numbers of female students studying computer science is a well-known problem in most of the western countries. The dominant perception about computer science field considered it as a masculine domain. In contrast, this study was performed in the IT department where female students are dominant compared to male students. The purpose of this study is to explore the influence of different factors on female students in choosing a career in the IT field. A survey was deployed to collect responses of female students in the IT department. The results show that female students are interested in computer science stream and nullify the dominant perception of computer science as a masculine domain. They want to learn technology, become an active member of the digital native world, and interested in coding literacy.